2017
DOI: 10.20959/wjpps20176-9409
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rogor Insecticide on Haematological Parameters of Fresh Water Fish, Cirrhinus Mrigala

Abstract: In developing countries natural water may be contaminated by untreated wastes ofindustrial, domestic and agricultural origin containing various metallic compounds and some pesticides, herbicides, insecticides and fungicides. Due to the bio accumulative and non-biodegradable properties of these compounds it constitutes a core group of aquatic pollutants. Some of these pollutants are known to accumulate in plant and animal tissues to very high levels, causing a potential toxic hazard to the primary organisms hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…The significant decrease in the in the WBC compared to the control observed in the present study is contrary to the findings of Nwani et al (2015) who reported a significant increase in white blood cell. This differences in the profile of WBC between the two studies is attributable to the difference in fish species, age, the cycle of sexual maturity and health condition of the fish (Vaiyanan et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…The significant decrease in the in the WBC compared to the control observed in the present study is contrary to the findings of Nwani et al (2015) who reported a significant increase in white blood cell. This differences in the profile of WBC between the two studies is attributable to the difference in fish species, age, the cycle of sexual maturity and health condition of the fish (Vaiyanan et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, American kestrels ( Falco sparverius ) fed a diet containing up to 448 ppm Pb showed no change in PCV (Custer et al, 1984; Franson et al, 1983). However, carp ( Cirrhinus mrigala ) exposed to sublethal amounts of Ni had significantly decreased PCV (Parthipan & Muniyan, 2013). This indicates some toxic heavy metals like Ni influence PCV while others like Pb may not.…”
Section: Resultsmentioning
confidence: 99%